Evaluation of Composting Technology Cooperation in Southeast Asia: DAC-Based Analysis and Comparison with GIZ - Makoto Osuga (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
This study conducts a cross-case analysis of compost-related technical cooperation projects implemented by the Japan International Cooperation Agency (JICA) in Southeast Asia, applying the six OECD/DAC evaluation criteria (relevance, coherence, effectiveness, efficiency, impact, and sustainability). The analysis covers six projects in Indonesia, Malaysia, Thailand, and Vietnam. First, publicly available ex-post evaluation reports were analysed through close reading of report narratives and cited evidence. Second, semi-structured interviews with stakeholders were used to triangulate documentary evidence and validate interpretations of the evaluation results. The findings suggest that project performance and sustainabilityare driven less by the technical sophistication of composting systems per se than by institutional fit and the design of local participation. As a comparative reference, the study also examines three cases under the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ)’s ProSoil programme. The comparison indicates that GIZ’s strategic combination of standardised ‘ready-made’ equipment and a long-term programme framework contributed to higher scores on efficiency and sustainability, whereas selected JICA projects demonstrated relative strengths in contextual adaptation and communityengagement. Overall, the results imply that effective compost technology cooperation requires project designs that explicitly integrate institutional conditions and an appropriate support horizon, in addition to technical content.